"Doctors Shouldn't Underestimate the Power that they Have": NZ Doctors on the Care of the Dying Patient. (May 2017) - Malpas, Phillipa Jean; Mitchell, Kay
Rapidly aging populations and increased prevalence of chronic rather than acute illnesses have seen growing public and professional interest in medical decision making at the end of life and greater attention being paid to the factors that influence how individuals make such decisions. This study comprised 2 components: The first, a postal survey, based on the Remmelink questionnaire was sent in May 2013 to 3420 general practitioners (GPs) in New Zealand. Results from this component are reported elsewhere. The second component (reported here) sought information by inviting GPs to ring a free-phone number to be interviewed about their experiences caring for their dying patients. Interviews were recorded then transcribed with identifying information deleted to preserve anonymity. With an aging population, the provision of end-of-life care will increase in general practice. There is no doubt that hospice and specialist palliative care have transformed the quality of care for the dying and their families in New Zealand. However, while respondents in this study seemed realistic about what palliative care can and cannot achieve, patients and their families may have unrealistic expectations of both hospice and palliative medicine. Many GPs appear confused over the legality of the assistance they provide to the terminally ill, concerned that actions such as increasing medication to address refractory symptoms, or stopping food and fluids may put them at risk of legal censure when they foresee that their actions may hasten death.